The Cultural Critic – A Decal? (KULT_online, 2013)
The dissertation of the historian Theo Jung published in 2012 provides extensive and convincing evidence for the thesis raised by Georg Bollenbeck in 2007 that modern cultural criticism emerges in the context of the temporalization of concepts (Koselleck) in the late 18th century. He also shows that historically oriented criticism of contemporary civilization arises and can be described as a discourse, i.e. a supra-individual mode of speech. Unfortunately, this approach widely conceals the fact that the cultural criticism of enlightenment is more than the formal subject position of the worry-wart but can be differentiated and appreciated philosophically as well, as former scholarship has shown.